A walk through the 20th century with Bill Moyers [videorecording] the democrat and the dictator - Moyers, Bill. (Beverly Hills, Calif. Public Broadcasting Service, 1990)
Bill Moyers explores the differences of Franklin D. Roosevelt and Adolf Hitler and the similar circumstances they faced in their struggle to control the world events.
Created and developed by the Corporation for Entertainment and Learning, Inc. and Bill Moyers, 1982.
VHS.
Keywords: Roosevelt, Frank Delano -- 1858-1919.; Hitler, Adolf -- 1889-1945.